Directive Speech Acts of Street Vendors at Mardika Market, Ambon - Wally, Firman; Somelok, Grace; Latupeirissa, Elsa (Universitas Pattimura, 2021)
This research is conducted due to the researcher's keen interest in the sales practices of street sellers in Mardika Market in Ambon. They actively employ strategically prepared language to get potential consumers to view their merchandise, rather than passively awaiting customers. This research theoretically enhances the language corpus, especially for directed speech acts in pragmatic analysis. This research can enhance readers' understanding of the impact of directed speech acts on others. The advantages for the researcher include gaining insights into the types of directive utterances typically employed by street apparel vendors, while other researchers may utilize this as a foundation for further investigations into directive speech actions in various studies. This study employs a qualitative research methodology. The research data for this study comprises utterances classified as directive utterances, which include ordering, requesting, inviting, proposing, advising, and challenging forms. The data sourcesfor this research are the narratives of street vendors at Mardika Market in Ambon. The employed data collection methods included observation, recording, field notes, and documentation. This study employed data reduction, data display, and conclusion drafting as its analytical methodologies. The researcher employed triangulation procedures involving theory and sources to verify thedata's veracity. Field data revealed that street clothing vendors at Mardika Market in Ambon employed six types of directive speech acts: ordering or commanding (two instances), requesting (four instances), inviting (seventeen instances), suggesting or advising (five instances), demanding (one instance),and challenging (four instances).